Towards the acceptance of a Prompt Engineering-based Approach to Build Proto-personas during Product Discovery - Ayach, Fernando Ribeiro; Fontão, Awdren (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2024: Anais Estendidos do XV Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2024.4096, 2024)
Product discovery approaches such as Lean Inception (LI) typically span five days (40 working hours). During LI, the participants create and refine proto-personas during four working hours to understand user needs. Proto-personas are preliminary representations of ideal users that guide initial design discussions. The accuracy of the generated proto-personas has been counter-intuitive due to the limited time. There is a gap in exploring the use of prompt engineering and proto-persona strategies to support the Product Discovery approaches. We report an exploratory case study where six participants used a prompt engineering-based approach to generate proto-personas in Product Discovery (LI). Participants accepted our approach well. Our approach used an average of 11 minutes of working hours (SD ≈ 2.24 minutes), traditionally this time in LI is four hours.